1996
DOI: 10.1007/s004410050540
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative investigation of the effects of neonatal capsaicin treatment on vagal afferent neurons in the rat

Abstract: The sensory cells of the nodose and jugular ganglia of the rat have been quantitatively evaluated in longitudinal paraffin sections. The right vagal ganglia contain significantly more neurons than the left, particularly neurons with somata having sectioned areas 200-400 microm2 and longest diameters 15-25 microm. Such neurons appear to be homogenously distributed because sections of the right vagal ganglia did not show specific areas of neuronal density compared with those of the left. Neonatal capsaicin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
4
8
1
Order By: Relevance
“…Taken together with our results, these data suggest that the adult NG reveal quantitatively comparable capsaicin-induced damage to the NG of neonates. In contrast to our results, however, Carobi (1996) found no restoration of neuronal number between the time of neonatal capsaicin treatment (2 days postnatal) and adulthood. Our finding that NG neuronal number is restored to control levels within 60 days after capsaicin treatment of adult rats suggests that the adult rat retains precursor cells capable of replacing lost neurons by a process involving DNA synthesis and cell division.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Taken together with our results, these data suggest that the adult NG reveal quantitatively comparable capsaicin-induced damage to the NG of neonates. In contrast to our results, however, Carobi (1996) found no restoration of neuronal number between the time of neonatal capsaicin treatment (2 days postnatal) and adulthood. Our finding that NG neuronal number is restored to control levels within 60 days after capsaicin treatment of adult rats suggests that the adult rat retains precursor cells capable of replacing lost neurons by a process involving DNA synthesis and cell division.…”
Section: Discussioncontrasting
confidence: 56%
“…Our present data does not allow us to determine the degree to which these two mechanisms may contribute to the expression of VR1 in our system. The only previous quantification of capsaicin-induced destruction of NG neurons (Carobi, 1996) reported that adult rats injected with capsaicin as neonates sustained a 70% reduction in total NG neuronal number compared to untreated controls. Taken together with our results, these data suggest that the adult NG reveal quantitatively comparable capsaicin-induced damage to the NG of neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Carobi [18] showed that following neonatal capsaicin administration to rats, only a 30% reduction was observed in the number of nodose ganglion neurons, compared to the controls. In addition to that, although 99% of abdominal vagal fibers have been shown to be small unmyelinated c-fibers [19], Berthoud et al [20] reported the existence of capsaicin-resistant afferent vagal fibers in different areas of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Since the amygdala also receives afferent inputs from the NTS [32], this route could be involved in at least part of food allergy-induced cfos expression in the CeA, even considering the lower activation seen in the NTS of capsaicin-treated animals. Despite the fact that neonatal capsaicin has been shown to destroy only 30% of the number of vagal neurons in the nodose ganglia [7] and 41 -75% of unmyelinated fibers in spinal cord roots [19], the present results lead us to suggest that additional mechanisms, apart from the capsaicin-sensitive C-fibers, are involved in food allergy signaling to specific brain areas. This suggestion is in accordance with our previous data showing that, albeit diminishing the magnitude of food aversion in allergic mice, capsaicin treatment was not able to block its development [3].…”
Section: Discussionmentioning
confidence: 78%